Contextualizing the embodied information practices of the devotees of Apung Lucia's Kuraldal - Espiritu, Anna Divine D.
The Kuraldal festival is an enduring celebration in Sasmuan, Pampanga, and is known to be the oldest and longest-running event dating back to the Hispanic era. The festival's essence revolves around the miraculous nature of Apu Lucia, where devotees venerate her for her ability to grant prayers. This resonated deeply with me, who has this genuine interest in this kind of festivities and yearns for blessings. My newfound experiences and curiosities from participating in the Kuraldal led to this academic pursuit. The study aimed to contextualize the embodied information practices of the devotees by exploring their experiences and recollections. They are the missing link between the past and present, given the scarcity of historical records. To provide a more thorough knowledge of this cultural phenomenon, the study contextualizes the embodied information activities within the community. Purposive sampling is used to identify important informants who are actively involved in the festival's organization.